2002
DOI: 10.1128/jb.184.17.4912-4919.2002
|View full text |Cite
|
Sign up to set email alerts
|

LasR, a Transcriptional Activator of Pseudomonas aeruginosa Virulence Genes, Functions as a Multimer

Abstract: The Pseudomonas aeruginosa LasR protein functions in concert with N-3-oxo-dodecanoyl-L-homoserine lactone (3O-C 12 -HSL) to coordinate the expression of target genes, including many genes that encode virulence factors, with cell density. We used a LexA-based protein interaction assay to demonstrate that LasR forms multimers only when 3O-C 12 -HSL is present. A series of LasR molecules containing internal deletions or substitutions in single, conserved amino acid residues indicated that the N-terminal portion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
165
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(176 citation statements)
references
References 38 publications
10
165
0
1
Order By: Relevance
“…We observed a single peak with a radius of 3.15 nm (data not shown) corresponding to a molecular mass of 49.3 kDa. This finding suggested that purified LasR-3OC12-HSL exists as a dimer in solution, consistent with a genetic study showing that LasR functions as a multimer in vivo (30).…”
Section: Lasr Is a Dimer In Solutionsupporting
confidence: 72%
“…We observed a single peak with a radius of 3.15 nm (data not shown) corresponding to a molecular mass of 49.3 kDa. This finding suggested that purified LasR-3OC12-HSL exists as a dimer in solution, consistent with a genetic study showing that LasR functions as a multimer in vivo (30).…”
Section: Lasr Is a Dimer In Solutionsupporting
confidence: 72%
“…Both biofilm formation and pyocyanin production, two best known QS phenomena in P. aeruginosa [27], were not significantly changed when the CRISPR-Cas system was deleted (Supplementary information, Figure S8), suggesting that CRISPR-Cas system does not impact on host inflammatory responses through modulating the regulatory activity of LasR in QS. As all of the above-mentioned data were collected using bacteria from stationary phase (OD 600 ~2.0), we repeated certain key experiments using the OD 600 ~0.5 cultures (log phase) of PA14 strains ( Figure 6D-6F).…”
Section: Ral Repression Of Lasrmentioning
confidence: 97%
“…As LasR is the critical QS regulator [27], we compared the QS phenomenon between PA14 WT and the mutants. Both biofilm formation and pyocyanin production, two best known QS phenomena in P. aeruginosa [27], were not significantly changed when the CRISPR-Cas system was deleted (Supplementary information, Figure S8), suggesting that CRISPR-Cas system does not impact on host inflammatory responses through modulating the regulatory activity of LasR in QS.…”
Section: Ral Repression Of Lasrmentioning
confidence: 99%
“…Previous studies indicate that the binding of the autoinducer 3-oxo-C12-HSL stabilizes LasR and promotes its dimerization, thereby enabling the resultant homodimeic LasR-autoinducer complex to bind to its target DNA promoter and activate gene transcription (6,13,22,24,25). We have shown previously that QslA can associate with LasR and thus disturb its target DNA-binding ability (22).…”
Section: Resultsmentioning
confidence: 99%